Design of a top-lit up-draft micro-gasifier biomass cookstove by thermodynamic analysis and fluent modeling (2017)
ABSTRACT: In this work the complete thermo-mechanicaldesign of a biomass top-lit up-draft(TLUD) cookstoveis presented. A design methodology which isbased on mass and energy balances,geometry relations amongthe main dimensions of the cookstove,and fluent modelingis proposed. Threemodelsweredesigned, sized, and simulatedthrough computational fluiddynamics (CFD)conducted in ANSYS Fluent 15.0.7. These designs allowed analyzingthe effect of cookstove design, primary and secondary air inlets (diameter and air supply setup) required inthe gasification and combustion processes, respectively.Simulations indicatedthat compressed air is not a suitableway to supply the air flow for gasification and combustionstages, due to the poorvelocitydistribution across the grate and secondary holes. Therefore,the final stove design will operate with axial fansto favor a good mixture between biomass and the air in the gasification stage, and between producergas and the air in thecombustion zone. Operation with axial fans,in the final cookstove design,allowedobtaininga lowstandard deviation of air velocity through the grate holes and through secondary air ring holes (±0.13 m/s, and ±0.45 m/s, respectively), which entails a better cookstove performance. This air supply system,also presented combustion air velocities through the secondary ring holes according to theones reported in the literature (3.02 m/s), which isimportant for the suitable air and producer gas mixing.